Quality by design: improving pre-stressed reinforcement for concrete railroad ties via geometrical dimensioning and tolerancing - Haynes, Mark Davis (Kansas State University, 2015)
Quality is a result of product design and production control. Product design must maximize the ability to function across variations in production and environment. Production control must monitor and maintain the key design characteristics necessary for the intended function. Failure to do so results in premature part failure and increased costs. This has occurred in the production of modern cross ties. By designing quality into the product and production process, performance is maximized. This research presents a methodology for incorporating quality into the product design and production process. For product design, a relationship between product performance and design parameters is established by modeling techniques. These models provide a means to redesign the product to maximize performance and to understand the sensitivity of the design to fluctuation in production and environment. These models also establish the key design parameters that are critical for sustaining quality. For production, a method of monitoring the key design parameters is presented that provides an affordable means of automated inspection. Automated inspection removes operator error from the inspection process and allows for greater sampling rates to be achieved. The methodology presented allows for a potential of 100% inspection to be achieved with minimal impact to production costs. The research is applied to the analysis and quality control of pre-stressing steel reinforcement for concrete cross-ties. This application provides an opportunity to test and verify the research findings on a real world problem. Novel automated 3D spatial analysis algorithms are presented. This research furthers the state of the art of performing Geometrical Dimensioning and Tolerancing (GD&T). A cost effective method of non-contact surface profiling was developed with high resolution and high density surface profiles. The combined research findings present a methodology of achieving quality by design.
Keywords: Geometrical Dimensioning and Tolerancing; Concrete Railroad Ties; Prestressing Steel Reinforcement Wire; Non-contact 3D scanning and inspection; Metrology; Quality Control; Civil Engineering (0543); Engineering (0537); Industrial Engineering (0546)